2022
DOI: 10.1096/fj.202200919r
|View full text |Cite
|
Sign up to set email alerts
|

The novel sustained 3‐hydroxybutyrate donor poly‐D ‐3‐hydroxybutyric acid prevents inflammatory bowel disease through upregulation of regulatory T‐cells

Abstract: Inflammatory bowel disease (IBD) is a chronic persistent intestinal disorder, with ulcerative colitis and Crohn's disease being the most common. However, the physio-pathological development of IBD is still unknown. Therefore, research on the etiology and treatment of IBD has been conducted using a variety of approaches. Short-chain fatty acids such as 3-hydroxybutyrate (3-HB) are known to have various physiological activities. In particular, the production of 3-HB by the intestinal microflora is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…PHB is a biodegradable polyester that degrades in soil in the following order: oligomer, dimer, and monomer (3‐HB) 30 . In our previous study, we found that the concentration of 3‐HB in feces and blood was increased after PHB administration 22 . These suggest that gut microbiota, as well as soil bacteria, can degrade PHB to the monomer 3‐HB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PHB is a biodegradable polyester that degrades in soil in the following order: oligomer, dimer, and monomer (3‐HB) 30 . In our previous study, we found that the concentration of 3‐HB in feces and blood was increased after PHB administration 22 . These suggest that gut microbiota, as well as soil bacteria, can degrade PHB to the monomer 3‐HB.…”
Section: Discussionmentioning
confidence: 99%
“…30 In our previous study, we found that the concentration of 3-HB in feces and blood was increased after PHB administration. 22 These suggest that gut microbiota, as well as soil bacteria, can degrade PHB to the monomer 3-HB. In this study, we investigated the prebiotic effects of PHB in C57BL/6N and ob/ob mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The profound influence of diet on the microbiome and the emerging central role of the microbiome on human health suggest that modulation of the microbiome prior to surgery may be a scientifically rational and practical approach to preventing postoperative complications [20]. Emerging evidence suggests that a high fiber, plant based low fat diet provides key substrates for the intestinal microbiota to produce metabolites such as tryptophan and short chain fatty acids (butyrate, propionate, acetate) each of which have profound effects on epithelial metabolism and the immune system at both the local level and systemically [21][22][23].…”
Section: Diet the Microbiome And Anastomotic Leakmentioning
confidence: 99%